Neutralization Escape by SARS-CoV-2 Omicron Subvariant BA.2.86 - Ninaad Lasrado; Ai‐ris Y. Collier; Nicole P. Hachmann; Jessica Miller; Marjorie Rowe; Eleanor Schonberg; Stefanie L. Rodrigues; Austin LaPiana; Robert C. Patio; Trisha Anand; Jana Fisher; Camille R. Mazurek; et al. (2023)
ABSTRACT The continued evolution of SARS-CoV-2 may lead to evasion of vaccine immunity and natural immunity. A highly mutated Omicron variant BA.2.86 has recently been identified with over 30 amino acid changes in Spike compared with BA.2 and XBB.1.5. As of September 4, 2023, BA.2.86 has been identified in 37 sequences from 10 countries, which is likely an underestimate due to limited surveillance. The ability of BA.2.86 to evade NAbs compared with other currently circulating Omicron variants remains unknown. Our data show that NAb responses to BA.2.86 were lower than to BA.2 but were comparable or slightly higher than to the current circulating recombinant variants XBB.1.5, XBB.1.16, EG.5, EG.5.1, and FL.1.5.1.